Distinguishing attosecond electron–electron scattering and screening in transition metals - Chen, Cong; Tao, Zhensheng; Carr, Adra; Matyba, Piotr; Szilvási, Tibor; Emmerich, Sebastian; Piecuch, Martin; Keller, Mark; Zusin, Dmitriy; Eich, Steffen; Rollinger, Markus; You, Wenjing; et al. (My University, 2017)
Electron–electron interactions are the fastest processes in materials, occurring on femtosecond to attosecond timescales, depending on the electronic band structure of the material and the excitation energy. Such interactions can play a dominant role in light-induced processes such as nano-enhanced plasmonics and catalysis, light harvesting, or phase transitions. However, to date it has not been possible to experimentally distinguish fundamental electron interactions such as scattering and screening. Here, we use sequences of attosecond pulses to directly measure electron–electron interactions in different bands of different materials with both simple and complex Fermi surfaces. By extracting the time delays associated with photoemission we show that the lifetime of photoelectrons from the d band of Cu are longer by ∼100 as compared with those from the same band of Ni. We attribute this to the enhanced electron–electron scattering in the unfilled d band of Ni. Using theoretical modeling, we can extract the contributions of electron–electron scattering and screening in different bands of different materials with both simple and complex Fermi surfaces. Our results also show that screening influences high-energy photoelectrons (≈20 eV) significantly less than low-energy photoelectrons. As a result, high-energy photoelectrons can serve as a direct probe of spin-dependent electron–electron scattering by neglecting screening. This can then be applied to quantifying the contribution of electron interactions and screening to low-energy excitations near the Fermi level. The information derived here provides valuable and unique information for a host of quantum materials.
Keywords: Electron–electron interaction; photoemission spectroscopy; charge scattering; advanced quantum materials